2020
DOI: 10.31004/cendekia.v4i1.166
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kesalahan Siswa Kelas XI Pada Materi Trigonometri

Abstract: Penelitian ini bertujuan untuk mengetahui kesalahan siswa dalam menyelesaikan soal trigonometri serta faktor penyebabnya. Jenis penelitian ini adalah deskriptif kualitatif. Subjek penelitian ini adalah 12 siswa kelas XI MIPA 3 di MAN Kota Cimahi. Teknik pengumpulan data menggunakan tes dan wawancara. Teknik analisis data melalui tiga tahapan yaitu reduksi data, penyajian data, serta verivikasi data dan penarikan kesimpulan. Kerangka analisis yang digunakan berdasarkan indikator kesalahan oleh hadar, yaitu: kes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 2 publications
1
2
0
5
Order By: Relevance
“…Based on previous research and the results of observations made in mathematics learning in Class X AKL 1 SMK PGRI 2 Kediri in April 2021, it was found that many students complained that mathematics was difficult, the difficulty experienced by students was to apply the trigonometric comparison value formula on a right triangle to the problem thus causing errors in problem solving. According to Kariadinata in (Rachman, 2020) argued that trigonometry is one part of mathematics related to angles and comparisons of trigonometric values that requires accuracy and foresight in thinking. If errors are not immediately addressed, it will have an impact on student achievement, therefore as a solution it is necessary to analyze the causes of errors based on Watson's criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous research and the results of observations made in mathematics learning in Class X AKL 1 SMK PGRI 2 Kediri in April 2021, it was found that many students complained that mathematics was difficult, the difficulty experienced by students was to apply the trigonometric comparison value formula on a right triangle to the problem thus causing errors in problem solving. According to Kariadinata in (Rachman, 2020) argued that trigonometry is one part of mathematics related to angles and comparisons of trigonometric values that requires accuracy and foresight in thinking. If errors are not immediately addressed, it will have an impact on student achievement, therefore as a solution it is necessary to analyze the causes of errors based on Watson's criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Pendidikan adalah proses belajar mengajar yang wajib diperoleh setiap individu baik secara formal maupun informal (Kaswar & Nurjannah, 2021). Pendidikan merupakan salah satu faktor penting dalam upaya peningkatan sumber daya manusia yang dapat meningkatkan kualitas hidup bangsa (Nurjannah et al, 2021;Rachman & Saripudin, 2020). Pendidikan dapat ditempuh salah satunya ialah dengan bersekolah (Kamalia et al, 2020).…”
Section: Pendahuluanunclassified
“…Pendidikan merupakan proses belajar dan pembelajaran yang bersifat formal dan informal yang harus dilalui oleh setiap individu (Hamalik, 2009). Dalam meningkatkan sumber daya manusia, pendidikan merupakan faktor utama yang dapat meningkatkan kualitas hidup manusia (Hamalik, 2009;Rachman & Saripudin, 2020). Implikasinya, sekolah merupakan salah satu wadah dalam menempuh pendidikan.…”
Section: Pendahuluanunclassified